The Visible Confederacy : Images and Objects in the Civil War South - Brooks, Ross A. (Ross Andrew), 1958- (Book collections on Project MUSE., 2019)
"The Visible Confederacy is a comprehensive analysis of the commercially and government-generated visual and material culture of the Confederate States of America. While historians have mainly studied Confederate identity through printed texts, this book shows that Confederates also built and shared a sense of who they were through other media: theatrical performances, military clothing, manufactured goods, and an assortment of other material. Examining previously understudied and often unpublished visual and documentary sources, Ross A. Brooks provides new perspectives on Confederates' sense of identity and ideas about race, gender, and independence, as well as how those conceptions united and divided them"--